2004
DOI: 10.1097/01.brs.0000142222.62203.67
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Tissue Loads and Spine Stability While Performing Commonly Prescribed Low Back Stabilization Exercises

Abstract: Quantification of the calibrated muscle activation levels together with low back compression and resultant stability assists clinical decisions regarding the most appropriate exercise for specific patients and specific objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
168
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 22 publications
11
168
2
9
Order By: Relevance
“…The method includes increasing the frequency of exercises to heighten the intensity of resistance and increasing the support instability degree using a theraball, vestibular balance board, and form roll 4) . In a study on the stability of muscle loads and the spine in healthy adults while performing lumbar stabilizer exercises, Kavcic et al 5) reported that the bridging exercise with the right leg lift, bridging exercise with the abdominal curl, side bridging exercise with right isometric side support, and bridging exercise posture are highly related to the muscle activity of the rectus abdominis. It is not the specific activity of the muscle that is important in spine stability, but rather, the harmonious coordination of the trunk muscles 6) .…”
Section: Introductionmentioning
confidence: 99%
“…The method includes increasing the frequency of exercises to heighten the intensity of resistance and increasing the support instability degree using a theraball, vestibular balance board, and form roll 4) . In a study on the stability of muscle loads and the spine in healthy adults while performing lumbar stabilizer exercises, Kavcic et al 5) reported that the bridging exercise with the right leg lift, bridging exercise with the abdominal curl, side bridging exercise with right isometric side support, and bridging exercise posture are highly related to the muscle activity of the rectus abdominis. It is not the specific activity of the muscle that is important in spine stability, but rather, the harmonious coordination of the trunk muscles 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, sitting balance is managed by an interaction between the global muscle system and the local muscle system: global muscles control the movement of the trunk, whereas local muscles assist and stabilize the global muscles. For this interaction, strength and endurance of the muscles around the trunk are needed 3) .…”
Section: Introductionmentioning
confidence: 99%
“…A partir destes resultados, pode-se sugerir que a atividade do multífido está relacionada com o aumento da extensão de tronco e com a mudança de posição pélvica de retroversão para neutra, e de neutra para a anteversão, coerente com o seu papel como músculo local, isto é, responsável pelo controle da estabilidade e da curvatura sagital da coluna lombar, na teoria de Bergmark (1989) 71 33 Alguns métodos fisioterapêuticos 22,24,85,97,139 vêm preconizando a escolha de exercícios, principalmente nas fases iniciais do processo de reabilitação de disfunções lombares, baseando-se na predominância de ação de músculos locais sobre os globais, na concepção de Bergmark (1989) 71 . Baseados em estudos "in vitro", "in vivo" e modelagem 22 encontrou um maior índice de relação entre oblíquo interno e reto do abdome (de aproximadamente 8), para a posição de apoio assimétrico (extensão do tronco em decúbito dorsal, com apoio em um só membro inferior).…”
Section: Discussionunclassified
“…Esta posição vem sendo estudada para o condicionamento da musculatura extensora do tronco, para o aumento gradual da carga compressiva sobre a região lombar, por meio do acréscimo de variações na posição, como a extensão de um membro inferior e ainda de um membro superior contralateral, e para a estabilização do tronco, de maneira geral 22,23,[32][33][34][35][36][37][38] .…”
Section: Introductionunclassified
See 1 more Smart Citation